2004
DOI: 10.1039/b400398e
|View full text |Cite
|
Sign up to set email alerts
|

Early molecular events in the photoactive yellow protein: role of the chromophore photophysics

Abstract: We report a comparative study of the isomerization reaction in native and denatured photoactive yellow protein (PYP) and in various chromophore analogues in their trans deprotonated form. The excited-state relaxation dynamics was followed by subpicosecond transient absorption and gain spectroscopy. The free p-hydroxycinnamate (pCA(2-)) and its amide analogue (pCM(-)) are found to display a quite different transient spectroscopy from that of PYP. The excited-state deactivation leads to the formation of the grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 52 publications
(65 reference statements)
7
94
1
Order By: Relevance
“…For WT and its mutants, neither the fluorescence spectra 59-62 nor the stimulated emission exhibit significant dynamical Stokes shift within the time resolution of our apparatus. 5,11,29 The shift or reshaping of the other absorption bands cannot be fully excluded but, as discussed in a former letter, 11 we rather believe the triexponential decays of the SE signal to arise from the existence of groundstate conformational heterogeneities leading, upon excitation, to excited-state heterogeneities. This hypothesis is consistent with NMR studies of WT in solution, which show that the protein is found to have many different conformations.…”
Section: Time-resolved Transient Absorbance Spectramentioning
confidence: 96%
“…For WT and its mutants, neither the fluorescence spectra 59-62 nor the stimulated emission exhibit significant dynamical Stokes shift within the time resolution of our apparatus. 5,11,29 The shift or reshaping of the other absorption bands cannot be fully excluded but, as discussed in a former letter, 11 we rather believe the triexponential decays of the SE signal to arise from the existence of groundstate conformational heterogeneities leading, upon excitation, to excited-state heterogeneities. This hypothesis is consistent with NMR studies of WT in solution, which show that the protein is found to have many different conformations.…”
Section: Time-resolved Transient Absorbance Spectramentioning
confidence: 96%
“…Previous time-resolved pump-probe spectroscopy studies have been performed on hydroxycinnamic acids, though much of this work has been focused upon the archetypal p-coumaric acid (3-(4-hydroxyphenyl)-2-propenoic acid) as either the isolated molecule or a functionalized chromophore to mimic the photoactive yellow protein. [20][21][22][23][24][25][26][27] In these studies p-coumaric acid was excited to the first excited electronic state (1 1 pp*, S 1 ). The main relaxation pathway of the 1 1 pp* state was identified as a trans-cis photoisomerization resulting in the formation of the cisphotoproduct.…”
Section: Introductionmentioning
confidence: 99%
“…This complexity can be reduced if the chromophore in its true anionic, not neutral, structure can be studied free of perturbations. With model compounds, the solvent effect can be assessed by studying them in the solution phase (14)(15)(16)(17)(18). However, the nature of intramolecular change and the timescales involved are still unknown.…”
mentioning
confidence: 99%